Poly-ether-ether-ketone wear particles induce a pro-inflammatory phenotype in a human monocytic cell line - Shannon Jamieson; Shannon Jamieson; Philip Hyde; Patrick Card; David Deehan; John Kirby; Alison Tyson-Capper (Frontiers in Bioengineering and Biotechnology)
ObjectivesThe aim of this study was to assess potential pro-inflammatory responses induced in a human monocyte cell line by poly-ether-ether-ketone (PEEK) particles. Investigations also focussed on the role of toll-like receptor 4 (TLR4) and reactive oxygen species (ROS) in immune responses to PEEK.MethodsPEEK particles were generated using a four-station multi-directional pin-on-plate wear simulator and used to treat THP-1 macrophages for 24 h at dosages of 0.5–50 μm3 per cell. THP-1 cell supernatant was used for protein secretion analysis using ELISA and gene expression investigations using RT-qPCR. TLR4 inhibition was also achieved using CLI-095 by treating cells prior to PEEK exposure. ROS production was investigated following PEEK treatment. IL-1β secretion was investigated by treating PEEK-exposed cells to 5 mM ATP for 1 h in order to assess the role of the inflammasome.ResultsPEEK particles were not immediately cytotoxic to THP-1 macrophages and induced a significant increase in gene expression and protein secretion of IL-8, CCL2, CCL3, and CCL4 at the highest dose (p < 0.0001). This increase in pro-inflammatory genes and proteins was not inhibited following blockade of TLR4. ROS production was significantly upregulated in the PEEK-treated cells and IL-1β secretion was also significantly increased following the addition of ATP to PEEK-exposed THP-1 cells.ConclusionPEEK particles are capable of inducing a pro-inflammatory phenotype in a human macrophage cell line which is not a result of TLR4 activation. PEEK particles do act in a PAMP-like manner and are able to induce ROS production as well as initiate inflammasome activation.